KAJIAN TINGKAT KERUSAKAN PENCEMARAN DI SUNGAI KRUKUT - Yuni Sesempuli; Bambang Iswanto; Diana Irvindiaty Hendrawan (ITB Journal Publisher, LPPM ITB, 2020)
Abstract. The population growth with its activities causes pressure on the Krukut River. Load management of pollutants that enters the river is based on the self purification of the river. This study aims to analyze the river characteristics and degradation rate of Krukut River. Krukut River which is a research location has a length of ± 9.04 km. Characteristics of Krukut River has a type of small rocky riverbed and irregular with manning coefficient from 0.035 to 0.045. The depth ranging from 0,99 - 2 m, with a current velocity from 0,3 to 1,29 m/s. Krukut River discharge at 2,873-7,889 m3/sec. Streeter Phelps modeling to find out the constant rate of degradation of Krukut River which resulted in the value of DO and BOD. The rate of increase of dissolved oxygen (Ka) with the value of Ka range of 1,586-4,542 d-1, the standard value should be 1,494 d-1. The results of degradation rate (Kd) of the study obtained values range 0,285